Implementasi Bahan Ajar Pencemaran Lingkungan Berbasis Problem Based Learning terhadap Pemahaman Konsep Siswa - Uki, Nonci Melinda; Suharta, I Gusti Putu; Lasmawan, I Wayan (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This research aims to test the increase in students' conceptual understanding after using Problem Based Learning (PBL)-based environmental pollution teaching materials. The research method used is experimental research with a one group pretest-posttest design. Data was collected through learning outcomes tests and analyzed using the N-Gain test. The research results showed that the average understanding of students' concepts before using PBL-based environmental pollution teaching materials was 55.65 in the pretest, and after using these teaching materials, the average understanding of students' concepts increased to 76.65 in the posttest. Thus, it can be concluded that there is an increase in students' conceptual understanding after using PBL-based environmental pollution teaching materials. This increase is proven through gain analysis which shows that the average increase in students' conceptual understanding after using these teaching materials is 0.86, which is included in the high criteria.